Inadequate teacher content knowledge and what to do about it: Evidence from El Salvador - Aymo Brunetti; Konstantin Büchel; Martina Jakob; Ben Jann; Daniel Steffen (University of Bern, Department of Economics, 2021)
Good teachers are the backbone of a successful education system. Yet, in developing countries, teachers' content knowledge is often inadequate. This study documents that primary school math teachers in the department of Moraz'an in El Salvador only master 47 percent of the curriculum they teach. In a randomized controlled trial with 175 teachers, we further evaluate a computer-assisted learning (CAL) approach to address this shortcoming. After a five months in-service training combining CAL-based self-studying with monthly workshops, participating teachers outperformed their peers from the control group by 0.29σ, but this effect depreciated by 72 percent within one year. Our simulations show that the program is unlikely to be as cost-effective as CAL interventions directly targeting students.
Keywords: C93; I20; I21; I28; O15; 330; Education quality; teacher performance; teacher training; student learning; basic math education; computer-assisted learning